Analisis Sentimen Review Film Indonesia Berdasarkan Rentang Usia dengan Simple Moving Average untuk Optimasi Sistem Rekomendasi - Lestari, Sri; Pasaribu, Wealty Sweet Charollyn (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
The rapid growth of the Indonesian film industry has increased the number of audience reviews across various digital platforms. However, existing film recommendation systems remain general and do not consider demographic factors, particularly the age range of viewers. This study aims to analyze the sentiment of Indonesian film reviews based on audience age categories in order to optimize film recommendation systems. Primary data were collected through questionnaires distributed to respondents aged 13–30 years, supported by additional review data from social media and online platforms. The method applied is sentiment analysis combined with Simple Moving Average (SMA). The integration of age-based sentiment analysis with SMA has been shown to improve the accuracy and relevance of film recommendation systems. This study provides implications for streaming platform developers and film producers to consider age segmentation in distribution, promotion strategies, and quality improvement within the Indonesian film industry.